Variability and path co-efficient for yield and yield components in rice (Bangladesh Journal of Agricultural Research, 2016)
Twenty five rice varieties were evaluated for their variability with regard to yield and yield components. Estimates of heritability and genetic advance as per cent mean were also obtained for the above traits. In addition, studies on character associations and path co-efficients were also undertaken. The results revealed high variability, heritability and genetic advance as per cent mean for productive tillers per plant, number of tillers per plant, number of grains per panicle and number of filled grains per panicle, while days to maturity was recorded with high heritability coupled with low genetic advance as per cent of mean. Further, yield was observed to be positively associated with number of tillers per plant, productive tillers per plant, number of grains per panicle and number of filled grains per panicle. Among these, number of tillers per plant, productive tillers per plant and number of filled grains per panicle were noticed to exert high direct effects on grain yield per plant. High indirect effects of most of the traits were noticed mostly through productive tillers per plant indicating importance of the trait as selection criteria in crop yield improvement programmes.Bangladesh J. Agril. Res. 41(2): 259-271, June 2016